Calibration of Digital Cameras for Mobile Mapping Purposes - Parningotan Hasudungan Situmorang (Universitas Gadjah Mada, 2019)
The development of the use of non-metric digital cameras in the form of action cameras for collecting geospatial data has become very useful and supports the work of mobile mapping for making three-dimensional (3D) models. Each lens has an error in the formation of a projection design and also an error during production. For example in a fisheye lens, which has a distortion model, namely radial distortion, tangential distortion, and shifting of the optical center point. The camera is considered to be calibrated if the principal distance, principal point offset, and lens distortion parameters are known. The preparation stage that needs to be done on the mobile mapping work in making 3D models is camera calibration. This research aims to determine the value of internal orientation parameters of a digital camera (action camera) that is used for mobile mapping purposes. Camera calibration in Photogrammetry aims to determine the geometric model of the camera described by Interior Orientation Parameters (IOP), including focal length, shifting principle point (PP), distortion, and other parameters. The calibration method used is the test field calibration. The calibration activities carried out on digital cameras are by measuring targets in the field using coded targets from Agisoft software. The calibration process is also carried out when processing photo data with Agisoft Photoscan Professional software. Camera calibration results using bundle adjustment on Agisoft Photoscan Professional software produce IOP (Interior Orientation Parameter) parameters, namely principal distance (C), principal point offset (Xp, Yp), and lens distortion parameters (K1, K2, K3, P1 , P2, B1, B2). Based on the results obtained, it can be concluded that Maximum Observational Radial Distance Encountered is 1 mm.